Experimental Study on Eccentric Compressive Performance of Concrete Column Strengthened with CFRP Grid Reinforced ECC Matrix - Kangjian Lin; Yuhou Yang; Zhiwei Chen; Xiaoyan Sun; Hailong Wang (Advances in Civil Engineering)
Carbon-fiber-reinforced polymer (CFRP) grid and engineered cementitious composite (ECC) were combined in this study to strengthen concrete columns. The influences of the number of layers, the overlap length of CFRP grids, and the eccentricity on the bearing capacity and rigidity of reinforced concrete columns were determined. The results show that the principal failure of the reinforced column was debonding of external ECC from FRP grids at the compressive area, edges, or sides. Significant enhancement in the ultimate bearing capacity and rigidity of eccentrically loaded columns was observed after they were externally reinforced by CFRP grids and ECC; such enhancement increased with the number of reinforced layers. Eccentricity made little difference to the enhancement rate of bearing capacity when the number of reinforced layers was the same. At different eccentricities, the composite layers at the tensile area and the compressive area had different contributions to the bearing capacity. An effective bond and efficient stress transfer could be ensured as long as the overlap length between CFRP grids reached 120 mm.